Investigations on Berezan Island in 2014–2018 (Hermitage Museum Archaeological Expedition) - Chistov, Dmitry (Hyperboreus, 2019)
A survey of the excavations on the Berezan Island (the estuary of Dnepr and S. Bug) conducted by the Hermitage Museum Archaeological Mission in 2014–2018.